YAP-dependent induction of UHMK1 supports nuclear enrichment of the oncogene MYBL2 and proliferation in liver cancer cells - Wei, Teng; Weiler, Sofia Maria Elisabeth; Tóth, Marcell; Sticht, Carsten; Lutz, Teresa; Thomann, Stefan; Torre, Carolina de la; Straub, Beate Katharina; Merker, Sabine; Ruppert, Thomas; Marquardt, Jens; Singer, Stephan; et al. (Oncogene, 2019)
The oncogene yes-associated protein (YAP) is a key modifier of liver homeostasis and regulates mitosis in hepatocytes as well as in malignantly transformed cells. However, the question of how YAP supports cell proliferation in hepatocellular carcinoma (HCC) is not well understood. Here we identified U2AF momology motif kinase 1 (UHMK1) as a direct transcriptional target of YAP and the transcription factor forkhead box M1 (FOXM1), which supports HCC cell proliferation but not migration. Indeed, UHMK1 stimulates the expression of genes that are specific for cell cycle regulation and which are known downstream effectors of YAP. By using BioID labeling and mass spectrometry, the dimerization partner, RB-like, E2F and multi-vulval class B (DREAM) complex constituent MYB proto-oncogene like 2 (MYBL2, B-MYB) was identified as a direct UHMK1 interaction partner. Like YAP, UHMK1 stimulates nuclear enrichment of MYBL2, which is associated HCC cell proliferation and the expression of the cell cycle regulators CCNB1, CCNB2, KIF20A, and MAD2L1. The association between YAP, UHMK1, MYBL2, and proliferation was confirmed in YAPS127A-transgenic mice and human HCC tissues. In summary, we provide a model by which YAP supports cell proliferation through the induction of important cell cycle regulators in a UHMK1- and MYBL2-dependent manner.